(untitled) (Eurasian Journal of Ecology, 2018)
This article presents data on the distribution, abundance and lifestyle of large carnivorans living in the territory of Kazakhstan, based on publications and collected new materials from the various regions of the country. From large carnivores in the territory of the republic there are found representatives of the family of Canidae (the wolf – Canis lupus), Ursidae (the brown bear – Ursus arctos, 2 subspecies), Mustelidae (the wolverine – Gulo gulo) and Felidae (the lynx – Lynx lynx, 3 subspecies, the caracal – Caracal caracal, the snow leopard – Uncia uncia). Until the 1950s and 1970s there were also the red wolf (Cuon alpinus), tiger (Panthera tigris) and cheetah (Acinonyx jubatus). According to the analytical review, it can be seen that the range, as well as the abundance of most of these species of large carnivores, are greatly reduced. Nowadays, there are almost no full-scale researches on the distribution and abundance of most large carnivoran species. Moreover, since the data available so far are mostly obsolete or fragmentary, it is necessary and relevant to continue research on the biology and ecology of lar Key words: large carnivorans, distribution, habitats, abundance, lifestyle